Female song and vocal interactions with males in a neotropical wren - Hall, Michelle L.; Rittenbach, Maria R. D.; Vehrencamp, Sandra L. (Frontiers in Ecology and Evolution, 2015)
Bird song is thought to function primarily in same-sex competition, mate attraction, and reproductive stimulation of a partner. However, these conclusions are based largely on studies of the song of male birds in north-temperate species. We investigate female song in a Neotropical wren, Thryophilus pleurostictus, using observations and experiments to test the function of female song. Female banded wrens sang much less often than males, their songs were shorter, and their repertoire of song types was smaller. Females did not seem to sing for same-sex competition for resources or mates: female song rate did not increase in response to simulated intrusion, and females sang in response to less than one-third of playbacks simulating territorial intrusion by either unpaired or paired females. Territorial defense is important for both survival and reproduction in species that occupy all-purpose territories year-round, but female involvement in territorial defense was limited. Females were more likely to approach simulated intruders when their partner approached more closely, and were closer to their partner during playback simulating a pair of intruders, perhaps contributing to defense jointly with their partner. Females did not appear to use song to attract males for mating: only 25% of females sang in response to playback simulating an unpaired male during the nest-building period, and they were less likely to sing shortly before laying when they were more likely to be fertile. Female song in banded wrens seemed to be used primarily for communicating with their breeding partner: female songs overlapped or began within 1 s of a song by their partner more often than expected by chance, and male vocal behavior changed in response to song by their partner. However, the low rate of female song in banded wrens suggests this function does not select for song elaboration, consistent with the view that same-sex competition is the main driver of female song elaboration.